Evaluation of participatory assessment of people affected by the constrution of CastanhÃo DAM â CearÃ, Brazil. - Maria Eliane Sampaio Cortez (2014)
The construction of the dam CastanhÃo work of greater importance for economic and social development of the state of CearÃ, to constituting receiving the waters of the transposition of the SÃo Francisco River, had as one of the most significant impacts the population displacement in the area needed to deployment of this lake. To construct this work, were inundated 60,000 hectares, which located in the city of Jaguaribara and large number of dispersed population. This research constitutes a case study where the impacts were assessed in the living conditions of the population directly affected, in order to subsidize and or improve the methodologies used by the government in the actions of involuntary resettlement undertaken by him in order to print economic improvements and social to those affected by the implementation of water projects. This study was conducted with application of interviews and participatory evaluation workshop with the resident population,government officials and civil society leaders. In the sample survey were used as an indicator of income level, the views of respondents on the situation in terms of income, before and after resettlement, the implanted productive projects and the continuation of activities previously undertaken. Housing conditions, quality of life and participation of affected populations in planning and execution actions that affect the community were evaluated. From the analysis of the data and studies conducted conclude: As a result, the interviews and of evaluation workshop conducted found that the population actively participated in decisions regarding the whole process of resettlement, as choosing the location of the city, types of housing, supervision of construction, type of cemetery, among others. As a main point in this regard was emphasized unanimously the excellent performance of the multistakeholder group established by the government, which fulfilled the function to inform and mediate conflicts involving all issues concerning the construction of complex CastanhÃo,especially resettlement. Other relevant issues highlighted were the improvement of housing conditions and infrastructure the new town and the improvement of education and health services. Negative aspects were not emphasized structuring of the city in terms of jobs especially for the youth, loss of leisure space for the population and especially the increased use of drugs and crime; continuity of the training process and community participation in city life; implementation of productive activities with absorption of labor, especially aimed at youth; completion of the implementation of the activities planned by the still unfinished project. Especially with respect to the public sector, the great recommendation is to guarantee the compatibility of schedules in the implementation of activities / actions in the projects in a timely manner, so as not to jeopardize the results expected.